Evaluation In Islamic Education - Sri Bintang Abadi; Khoirunnisa Alfadhillah; Putri Salisatu Toyibah; Opik Taufik Kurahman; Dadan Rusmana (Penerbit Hellow Pustaka, 2025)
This research aims to analyze evaluations in Islamic education in order to find out the extent to which students have mastered their competencies. Evaluation in the view of Islamic education focuses on forming students' self-awareness after knowing what needs to be improved in their life journey. In preparing this article, researchers used qualitative methods with the type of library research. This type of qualitative research is research that produces information in the form of notes and descriptive data contained in the text being studied. The data used is by collecting books, journals and others related to evaluation in Islamic education. The collected data was analyzed using descriptive methods. The research results show that the way students learn is determined by the evaluation method, and vice versa, the evaluation method used by teachers is determined by the evaluation objectives. Evaluation must be carried out continuously (continuity). This last principle must carry out continuous evaluation but must not ignore the other evaluation principles. It is generally understood that students who can evaluate themselves are able to understand the extent of their religious abilities, their faith and their religious experience.